2011
DOI: 10.1182/blood-2010-10-314526
|View full text |Cite
|
Sign up to set email alerts
|

Plant homologue constitutive photomorphogenesis 9 (COP9) signalosome subunit CSN5 regulates innate immune responses in macrophages

Abstract: COP9 plays a role in plant innate immunity. The role of COP9 in mammalian innate immune responses is unknown. Here, we show that the COP9 signalosome subunit 5 (CSN5) is required for activation of proinflammatory kinases p38 and Erk and for down-regulation of the expression of genes regulated by nuclear factor E2-related factor 2. Mice with myeloid-specific CSN5 deficiency have lower mortality in polymicrobial sepsis. CSN5 is required for both Toll-like receptor (TLR) and reactive oxygen species-mediated dened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…With respect to CSN5, the clearness of the identified antiatherogenic (and antiinflammatory) effects is remarkable, as previous studies have also linked CSN5 to proinflammatory JNK/ AP1 signaling and proatherogenic LFA-1 integrin activation while counteracting inflammatory MIF activity (14)(15)(16). This may be the result of COP9 complex-associated vs. complexindependent activities.…”
Section: /Apoementioning
confidence: 89%
See 1 more Smart Citation
“…With respect to CSN5, the clearness of the identified antiatherogenic (and antiinflammatory) effects is remarkable, as previous studies have also linked CSN5 to proinflammatory JNK/ AP1 signaling and proatherogenic LFA-1 integrin activation while counteracting inflammatory MIF activity (14)(15)(16). This may be the result of COP9 complex-associated vs. complexindependent activities.…”
Section: /Apoementioning
confidence: 89%
“…CSN5 is the only CSN subunit with catalytic activity and acts as part of the holocomplex and independently of the CSN (11). Importantly, CSN5 has also been linked to inflammatory regulation (14)(15)(16). Whereas the conjugation of NEDD8 to cullins, termed NEDDylation, is required for an optimal ubiquitin ligase activity of the SCFs (17)(18)(19)(20), CSN-mediated deNEDDylation has been linked with the dissociation of the substrate-binding module from the SCF complex and with inhibition of SCF-mediated substrate ubiquitination in vitro (21,22).…”
Section: Significancementioning
confidence: 99%
“…For example, it has been reported that lipopolysaccharide-induced shock and polymicrobial sepsis induces early and greater mortality in Nrf2-deficent mice, which is related to the lethal innate immune response [44]. In contrast, transgenic mice with a decreased rate of Nrf2 degradation showed lower mortality in polymicrobial sepsis [45]. Consequences of the down-regulation of the Nrf2 host difference mechanism still remain to be fully explored.…”
Section: The Chain Of Redox Eventsmentioning
confidence: 99%
“…Furthermore, Jab1 overexpression has been implicated in the initiation and progression of various cancers, suggesting an oncogenic role (Shackleford and Claret, 2010). The constitutive deletion of Jab1 in mice results in early embryonic lethality by E8.5 with impaired proliferation and accelerated apoptosis (Tomoda et al, 2004;Tian et al, 2010), whereas cell typespecific deletions of Jab1 in T-cell, B-cell, or myeloid cells all lead to severe postnatal cell differentiation defects and increased apoptosis (Panattoni et al, 2008;Deng et al, 2011;Sitte et al, 2012). Thus, Jab1 plays essential roles both in general embryogenesis and in the differentiation of specific organs and tissues.…”
Section: Introductionmentioning
confidence: 99%